HIGH-RESOLUTION COMPUTED TOMOGRAPHY IN DIAGNOSING AND MONITORING VARIOUS INTERSTITIAL LUNG DISEASES - BHARAT JAIN; KAPIL VYAS; SRISHTI; MANISH ASUDANI; KARISHMA JARIWALA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Interstitial lung diseases (ILDs) are difficult to diagnose and require accurate imaging methods. The purpose of this work is to investigate ILD patterns and their relationships to pulmonary function using high-resolution computed tomography (HRCT). The aim is to augment our comprehension of ILDs, thereby facilitating customized approaches to diagnosis and treatment Methods: We recruited 50 ILD patients with radiological and clinical issues for a single-center trial. Spirometric data, symptoms, and demographics were recorded on comprehensive patient proformas. An expert radiologist used a Siemens-Somatom 6-slice CT scanner to analyze the HRCT. Pulmonary function indices were obtained using spirometry, which was carried out using a Medisoft Spiro Air spirometer. Results: In fifty cases with ILD, common features on HRCT were uneven pleural borders, ground glass opacities, and septal/subpleural lines. The complex interaction between radiological symptoms and respiratory health was highlighted by the substantial correlations seen between HRCT severities; extent scores, and reduced pulmonary function. Conclusion: The study reinforces the necessity for individualized diagnostic and treatment methods in the ILD respiratory landscape by providing detailed insights into their disease patterns and relationships.